Landslide hazard zoning in the Jerzu Hillside (Sardinia, Italy) - Ardau, F.; Barbieri, G.; Fantini, S. (Journal of Nepal Geological Society, 2000)
The landslide hazard zoning method described in this paper is a modification of the method developed by the Italian Geological Service for mapping geological hazards associated with gravitational instability. For this purpose, at first a preliminary zoning is done by dividing the study area into a discrete number of smaller units that have sufficiently similar susceptibility to instability. Semi-quantitative field surveys are then conducted in each unit to evaluate the geological, morphological, vegetative, and geotechnical factors, which con tribute to the hill slope susceptible to sliding. The final landslide hazard zoning is obtained by assigning a numerical weight to each factor in relation to the degree of instability determined. The weights assigned to these factors are then added up for each unit. The method was applied to the hillside of Jerzu in Sardinia (Italy), where landslides of varying dimensions are present. The validity of the proposed method was examined by comparing the resulting landslide hazard map with the actual distribution of landslides in the area.